ENHANCING PHYSICAL EDUCATION IN SECONDARY SCHOOLS THROUGH THE USE OF INTERACTIVE TRAINERS: A MODERN PEDAGOGICAL APPROACH (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
The transformation of educational systems in the digital era necessitates the integration of innovative technologies into traditional teaching practices. This study investigates the role of interactive trainers in enhancing physical education in secondary schools. Using a quasi-experimental design, the research compares traditional teaching methods with technology-assisted instruction. The findings demonstrate that interactive trainers significantly improve students’ physical performance, engagement, and motivation. The study contributes to the growing body of research on digital pedagogy and offers practical recommendations for educators and policymakers.